A systematic review of studies examining the relationship between resilience and physical asset management for water system - A.T., Rozman; W.R.A., Jiram; M.S.A., Rahman; A., Ismail; N.A., Azmi (2022)
The resilience in the water system can produce great benefits; one of the ideal ways to achieve resilience is through asset management. The purpose of this study is to systematically review the literature that presents the relationship between asset management and resilience. We searched multiple databases such as Emerald Insight, Sage Publication, Science Direct, Scopus, Taylor and Francis, and Wiley Online Library ranging from the year 2000 until the year 2020. The papers are written in English. A total of 7845 articles have been successfully identified and only 6 papers met the inclusion criteria of the study. The study has concluded that most of the previous research that discusses asset management and resilience are in groups dating 5 years back (2015-2019). Several features of physical asset management require further investigation that can enhance the resilience of the water system. The topic is relatively new and hopes to open a huge gap for research.